PENGAWASAN USAHA KARAOKE OLEH PEMERINTAH KOTA PEKANBARU SELAMA PANDEMI (COVID-19) TAHUN 2020 - Asep Afriansyah; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
During this pandemic, entertainment venues are one of the places that have the potential to gather crowds of people, with large crowds of people causing an increase in the spread of the Covid-19 virus. The existence of Karaoke entertainment in the city of Pekanbaru many violations that occurred during the Covid-19 pandemic. This study aims to determine the supervision of karaoke businesses by the Pekanbaru city government during the 2020 (Covid 19) pandemic. The approach used in this study is a qualitative approach with a type of descriptive research. The location of this research was carried out in karaoke entertainment in Pekanbaru City, with data collection techniques carried out by interviews and documentation. The results of this study are that the supervision carried out by the Covid-19 Task Force is still weak on the supervision of karaoke entertainment during the new normal period of the Covid-19 pandemic in Pekanbaru City and the implementation of standard health protocols by entertainment managers. There are several factors that influence it, including the quality of human resources, the lack of awareness of karaoke business owners, and the lack of budget factors. In the implementation of supervision, it has been running but is still not optimal, there are still violations of health protocols at karaoke entertainment venues during the new normal period of the Covid-19 pandemic in Pekanbaru City. Keywords : Supervision, Karaoke Entertainment, Covid-19.